Correlations between Visual Performance and Chorioretinal Variables after Vitrectomy for the Idiopathic Macular Hole. (28th December 2022) - Chen, Minfeng; Zheng, Chenchen; Liu, Yu; Chen, Feng; Xu, Dan; Lu, Fan
Abstract : Purpose . To investigate the relationships between visual function and the retinal and choroid microstructure in idiopathic macular hole patients after surgery. Methods . A prospective study investigated changes in the fundus structure and visual function in 16 macular hole patients before and after surgery. Patients' best-corrected visual acuity (BCVA) and retinal sensitivity were measured by an EDTRS visual chart and microperimetry (MP1), respectively. The thickness of the retina and the blood supply to the retina and superficial choroid were detected by OCTA, and the choroidal capillary blood flow density was analysed with MATLAB. The thickness of the choroid and the aperture size of the macular hole were detected by Heidelberg OCT. Results. Compared with before surgery and one month after surgery, the BCVA (3 months: 0.47 ± 0.27, before: 1.02 ± 0.22, 1 month: 0.66 ± 0.27, and P  < 0.05) and the central sensitivity of the retina (3 months: 14.88 ± 2.87 dB, before: 8.76 ± 3.27 dB, 1 month: 12.22 ± 3.30 dB, and P  < 0.05) were significantly improved three months after surgery. The change in BCVA was significantly correlated with the basal diameter ( r  = 0.677 and P  = 0.004), the minimum diameter ( r  = 0.585 and P  = 0.017), the macular hole cystoid height area index ( r  = −0.618 and P  = 0.011), the central macular hole index ( r  = −0.727 and P  = 0.001), the peripheral macular hole index ( r  = −0.758 and P  = 0.001), the central tractional hole index ( r  = −0.717 and P  = 0.002), the peripheral tractional hole index ( r  = −0.725 and P  = 0.001), and changes in the peripheral blood vessel density of the choroid capillary layer ( r  = 0.585 and P  = 0.0017). The change in central retinal sensitivity was correlated with the change in the superficial foveal avascular zone (FAZ; r  = 0.520 and P  = 0.039), change in the retinal superficial peripheral blood flow density ( r  = −0.503 and P  = 0.047), change in the deep FAZ ( r  = 0.599 and P  = 0.014), and change in the retinal deep peripheral blood flow density ( r  = −0.601 and P  = 0.014). Conclusions . The morphology of the macular hole as well as changes to the retinal and choroidal microstructure contributes to the recovery of visual function after surgery.